2002
DOI: 10.1017/s096702620200392x
|View full text |Cite
|
Sign up to set email alerts
|

Short-term adaptation of microalgae in highly stressful environments: an experimental model analysing the resistance ofScenedesmus intermedius(Chlorophyceae) to the heavy metals mixture from the Aznalcóllar mine spill

Abstract: The toxic spill of acid wastes rich in heavy metals\metalloids (AWHM) from the Aznalco! llar mine in April 1998, threatening the Don4 ana National Park, is considered to be the worst environmental disaster related to acute pollution in Spanish history. The aim of this work was to study the adaptation of microalgae (which play an important role as primary producers) from AWHM sensitivity to AWHM resistance by using the alga Scenedesmus intermedius as an experimental model. The Malthusian parameter (m) and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…As mentioned, this genotype likely possesses a mutation that makes it more tolerant of low pH. Because our communities were only exposed to acidic waters for five weeks, it is unlikely that this was a mutation arose de novo with acidification [58,59] and favoured genotypes would need to be present a priori for evolutionary shifts to occur at ecologically relevant timescales.…”
Section: Discussionmentioning
confidence: 94%
“…As mentioned, this genotype likely possesses a mutation that makes it more tolerant of low pH. Because our communities were only exposed to acidic waters for five weeks, it is unlikely that this was a mutation arose de novo with acidification [58,59] and favoured genotypes would need to be present a priori for evolutionary shifts to occur at ecologically relevant timescales.…”
Section: Discussionmentioning
confidence: 94%
“…Adaptation of cyanobacteria and algae, which are the principal primary producers of aquatic ecosystems, to environmental changes resulting from anthropogenic contamination (or even to extreme natural environments) seems to be the result of a rare event: the spontaneous mutation from sensitivity to resistance that occurs randomly prior to the cells coming into contact with the selective agent (Costas et al 2001;Ló pez-Rodas et al 2001;Baos et al 2002;García-Villada et al 2002FloresMoya et al 2005). The rate of mutation from G s fi G r (from 3.1 · 10 -7 to 3.6 · 10 -7 mutants per cell per generation) was one to two orders of magnitude lower than the mutation rates we have described (from 2.12 · 10 -5 to 1.76 · 10 -6 mutants per cell per generation) for the resistance to several biocides in other cyanobacterial and microalgal species (Costas et al 2001;Ló pez-Rodas et al 2001;Baos et al 2002;García-Villada et al, 2002, but of the same order of magnitude found for the resistance to sulphureous waters in the chlorophycean Spirogyra insignis (2.7 · 10 -7 mutants per cell per generation) (Flores-Moya et al 2005). Nevertheless, the pre-selective G s fi G r mutations are sufficiently frequent in M. aeruginosa populations to allow them to adapt to the presence of glyphosate in culture.…”
Section: Discussionmentioning
confidence: 99%
“…Different mechanisms, both at the individual and community level, can enable algae to tolerate physical, chemical, and biological stress. In fact, heavy metal pollution can induce community tolerance mechanisms through genetic adaptation (such as Pollution Induced Community Tolerance), by which tolerant and welladapted genotypes are selected (Harding & Whitton, 1976;Foster, 1982;Kelly & Whitton, 1989;Gustavson & Wängberg, 1995;Bérard et al, 1998;Admiraal et al, 1999;Ivorra et al, 2002;Baos et al, 2002). For example, Gomphonema parvulum seems to be able to adapt genetically to a wide range of physical and chemical stresses (Ivorra et al, 2002).…”
Section: Nutrientsmentioning
confidence: 99%